DAYA TARIK WISATA DAN DAYA DUKUNG KAWASAN WISATA DI TAMAN WISATA ALAM PULAU POMBO MALUKU TENGAH - Tjoa, Maxel; Lelloltery, Henderina; Puttileihalat, Maya (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
This research aims to determine the tourist objects and attractions in the Pombo Island Nature Tourism Park and also the carrying capacity of the Pombo Island tourist area. This research is a qualitative and quantitative descriptive research in the form of written words and analysis of tourist objects and attractions. The research results showed that there were 17 types of plants including seedlings, saplings, poles and trees. There are 23 types of birds found, there are also nesting habitats for gosard birds and hawksbill turtles which can be a tourist attraction. The calculation of the ecotourism carrying capacity index in the Pombo Island area has a value of 73.80%, indicating that the Pombo Island beach is